The Effectiveness of God- Inclined Spiritually Therapy on the Reduction of Depression and Anxiety and the Increase of Quality Life of Women with Breast Cancer in Tehran City - Vahhabi Meshak, Masoumeh; Mojtabaei, Mina (Applied Family Therapy Journal (AFTJ), 2022)
Aim: The Present article aimed to investigate the effectiveness of god-inclined therapy on the reduction of depression and anxiety and the increase of quality life of women with breast cancer(BC) in Tehran. Methods: The present research was implemented in quasi-experimental method with pre-test and post-test design, control group and follow-up. The statistical population were all women with breast cancer(BC) under treatment in ShahreRey hospital of Tehran during 2022; among them30 women were selected in voluntarily purposeful method and appointed in two groups of experimental and control. The instruments were consisted of Beck’s depression and anxiety questionnaires and World’s Health Organizational questionnaire of quality of life. The validity was confirmed by the experts and the reliability was estimated and approved through Cronbach Alpha (α>0.07). Prior to the treatment, the depression, anxiety and quality of life tests were implemented for both groups. The experimental group had received a God- Inclined Spiritually Therapy through eight sessions. The control group had not received any treatment. Both groups repeatedly answered to the questionnaires, after implementing the intervention in post-test and follow-up stages. The data was analyzed through between-within mixed variance analysis. Results: The results revealed that god-inclined therapy was effective in the reduction of depression (F=5.02, P=0.03) and anxiety (F=11.16, P=0.001) and the increase of women`s quality of life (F=25.52, P=0.001), which was stable after 45days in follow-up stage (p